2013
DOI: 10.5489/cuaj.1244
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of tamsulosin on the measurement of bladder wall thickness and International Prostate Symptom Score in benign prostatic hyperplasia

Abstract: Introduction: According to previous studies, aging, gender, bladder volume and pathological states, such as bladder outflow obstruction, affect bladder wall thickness (BWT). The aim of this study was to evaluate the correlation between BWT and the International Prostatic Symptom Score (IPSS) in patients with benign prostatic hyperplasia (BPH) before and after tamsulosin treatment. Methods: In this study, 60 BPH patients were included. After obtaining informed consent, data were gathered using questionnaires to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…18 In another study, improvements in voiding symptoms and decreases in BWT after tamsulosin treatment indicated that ultrasound measurements of BWT, with flow rate studies and IPSS, could be considered an outcome assessment tool in the pharmacologic treatment of BPH. 2 In the present study, we found a significant difference between BWT measured before and 6 months after alpha-blocker treatment with alfuzosin. There was a significant difference between pre-and post-treatment values with alfuzosin in terms of mean Qmax, Qave, IPSS, QoL score, and PVR.…”
Section: Karakose Et Alsupporting
confidence: 61%
See 2 more Smart Citations
“…18 In another study, improvements in voiding symptoms and decreases in BWT after tamsulosin treatment indicated that ultrasound measurements of BWT, with flow rate studies and IPSS, could be considered an outcome assessment tool in the pharmacologic treatment of BPH. 2 In the present study, we found a significant difference between BWT measured before and 6 months after alpha-blocker treatment with alfuzosin. There was a significant difference between pre-and post-treatment values with alfuzosin in terms of mean Qmax, Qave, IPSS, QoL score, and PVR.…”
Section: Karakose Et Alsupporting
confidence: 61%
“…Alpha-blocker treatment improves Qmax, Qave, IPSS, QoL score, and structural changes in bladder wall caused by lower urinary tract obstruction in patients with LUTS. 2,18 Ultrasound studies showed that alpha-blocker treatment decreases PVR and increases of Qmax, which correlated with decreases in bladder wall hypertrophy. 10 Alpha-blocker treatment with tamsulosin in men with prostatic hyperplasia decreased the ultrasound-estimated bladder weight (from 65 to 28 g).…”
Section: Karakose Et Almentioning
confidence: 99%
See 1 more Smart Citation